Eight-channel parallel transmit-receive system for 7 T MRI with optically controlled and monitored on-coil current-mode RF amplifiers - Gudino, Natalia (Magn Reson Med, 2020)
PURPOSE: To demonstrate a practical implementation of an eight-channel parallel-transmit system (pTx) for brain imaging at 7 T based on on-coil amplifier technology. METHODS: An eight-channel parallel transmit-receive system (pTx-Rx) was built with optimized on-coil switch-mode current RF power amplifiers. The amplifiers were optically controlled from an eight-channel interface that was connected to a 7 T MRI scanner. The interface also optically received a down-converted version of the coil current sensed in each amplifier for monitoring and feedback adjustments. RESULTS: Each on-coil amplifier delivered more than 100 W peak power and provided enough amplifier decoupling (< −15 dB) for the implemented eight channel array configuration. Phantom and human images were acquired to demonstrate practical operation of this new technology in a 7 T MRI. CONCLUSION: Further development and improvement of previously demonstrated on-coil technology led to successful implementation of an eight-channel pTx system able to deliver strong B(1) fields for typical brain imaging applications. This is an important step forward towards implementation of on-coil RF amplification for high field MRI.